PENEMPATAN SITUS -SITUS NEOLITIK DI DAS CIBEUREUM , LEBAK , BANTEN - Nurul Laili (Kemendikbud, 2019)
This paper is intended to examine more about the lives of neolithic supporters in West Java and can provide clues about patterns of human behavior in utilizing space for its activities. There are 19 neolithic sites along Das Cibeureum, spread over two subdistricts, namely Curugbitung and Maja. The results showed that the 19 sites were grouped. This paper uses the analysis of the nearest neighbor which considers several factors, including: (1) distance, (2) linkages (interactions), and (3) movements. Neolithic sites are in two districts, namely Curugbitung and Maja Districts. The conclusion from this paper is that the 19 sites are grouped. The grouping of neolithic sites is strongly influenced by the location of the river. This is due to the potential of the river as a transportation route and water provider for supporting living needs.